2011
DOI: 10.1051/m2an/2011045
|View full text |Cite
|
Sign up to set email alerts
|

On the convergence of generalized polynomial chaos expansions

Abstract: Abstract.A number of approaches for discretizing partial differential equations with random data are based on generalized polynomial chaos expansions of random variables. These constitute generalizations of the polynomial chaos expansions introduced by Norbert Wiener to expansions in polynomials orthogonal with respect to non-Gaussian probability measures. We present conditions on such measures which imply mean-square convergence of generalized polynomial chaos expansions to the correct limit and complement th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
313
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(323 citation statements)
references
References 45 publications
3
313
0
1
Order By: Relevance
“…[22]. As a word of caution, we can note that the work [23] showed that there exist probability measures, such as the lognormal one, which admit a family of orthonormal polynomials that however does not form a basis for L 2 ϱ (Γ ), i.e. there exist functions in L 2 ϱ (Γ ) that cannot be approximated with arbitrary precision by linear combinations of such orthonormal polynomials.…”
Section: Galerkin Polynomial Approximation In the Stochastic Dimensionmentioning
confidence: 99%
“…[22]. As a word of caution, we can note that the work [23] showed that there exist probability measures, such as the lognormal one, which admit a family of orthonormal polynomials that however does not form a basis for L 2 ϱ (Γ ), i.e. there exist functions in L 2 ϱ (Γ ) that cannot be approximated with arbitrary precision by linear combinations of such orthonormal polynomials.…”
Section: Galerkin Polynomial Approximation In the Stochastic Dimensionmentioning
confidence: 99%
“…This proposal is based on the following key fact: the weighting functions associated to the so-called Wiener-Askey scheme, that correspond to classical families of orthogonal polynomials, are identical to the probability density functions of some standard random variables. Recently, in [10] authors provide conditions under which gPC expansions converge in the mean-square sense to the correct limit, which constitutes an extension of paper of Cameron and Martin [7] where mean-square convergence of homogeneous chaos was established.…”
Section: Introductionmentioning
confidence: 92%
“…This property is fulfilled by probability distributions of uniform, Gaussian or beta type, for example. General distributions have to satisfy certain conditions, see [24], whereas a treatment of lognormal distributions can be found in [25]. Consequently, a function f ∈ L 2 (Π, ρ) exhibits a representation in the so-called polynomial chaos (PC), see [5],…”
Section: Polynomial Chaos Expansionmentioning
confidence: 99%
“…The quality of the MOR determines the magnitude of the term E 3 (s) in (24). Since the L 2 -norm of the probability space is employed, the MOR is required to be sufficiently accurate in subdomains of the parameters with relatively large probabilities.…”
Section: Error Analysismentioning
confidence: 99%